A constitutive BCL2 down-regulation aggravates the phenotype of PKD1-mutant-induced polycystic kidney disease. (11th September 2017) - Duplomb, Laurence; Droin, Nathalie; Bouchot, Olivier; Thauvin-Robinet, Christel; Bruel, Ange-Line; Thevenon, Julien; Callier, Patrick; Meurice, Guillaume; Pata-Merci, Noémie; Loffroy, Romaric; Vandroux, David; Costa, Romain D A; et al.
Abstract: The main identified function of BCL2 protein is to prevent cell death by apoptosis. Mouse knock-out for Bcl2 demonstrates growth retardation, severe polycystic kidney disease (PKD), grey hair and lymphopenia, and die prematurely after birth. Here, we report a 40-year-old male referred to for abdominal and thoracic aortic dissection with associated aortic root aneurysm, PKD, lymphocytopenia with a history of T cell lymphoblastic lymphoma, white hair since the age of 20, and learning difficulties. PKD, which was also detected in the father and sister, was related to an inherited PKD1 mutation. The combination of PKD with grey hair and lymphocytopenia was also reminiscent of Bcl2 −/− mouse phenotype. BCL2 gene transcript and protein level were observed to be dramatically decreased in patient peripheral blood T-cells and in his aorta vascular wall cells, which was not detected in parents and sister T-cells, suggesting an autosomal recessive inheritance. Accordingly, spontaneous apoptosis of patient T-cells was increased and could be rescued through stimulation with an anti-CD3 antibody. Direct sequencing of BCL2 gene exons, promoter and 3'UTR region as well as BCL2 mRNA sequencing failed in identifying any pathogenic variant. Array-CGH was also normal and whole exome sequencing of the patient, parents and sister DNA did not detect any significant variant in genes encoding BCL2-interacting proteins. miRNA array identified an up-regulation of miR-181a, which is a known regulator of BCL2 expression. Altogether, miR-181a-mediated decrease in BCL2 gene expression could be a modifying factor that aggravates the phenotype of a PKD1 constitutive variant.